Two-photon polymerization of optical microresonators for precise pH sensing - Anton V. Saetchnikov; Elina A. Tcherniavskaia; Vladimir A. Saetchnikov; Andreas Ostendorf (Light: Advanced Manufacturing)
Water monitoring, environmental analysis, cell culture stability, and biomedical applications require precise pH control. Traditional methods, such as pH strips and meters, have limitations: pH strips lack precision, whereas electrochemical meters, although more accurate, are fragile, prone to drift, and unsuitable for small volumes. In this paper, we propose a method for the optical detection of pH based on a multiplexed sensor with 4D microcavities fabricated via two-photon polymerization. This approach employs pH-triggered reversible variations in microresonator geometry and integrates hundreds of dual optically coupled 4D microcavities to achieve the detection limit of 0.003 pH units. The proposed solution is a clear example of the use-case-oriented application of two-photon polymerized structures of high optical quality. Owing to the benefits of the multiplexed imaging platform, the dual 4D microresonators can be integrated with other microresonator types for pH-corrected biochemical studies.